Linear and nonlinear effects of temperature and precipitation on ecosystem properties in tidal saline wetlands. Issue 10 (2nd October 2017) - Feher, Laura C.; Osland, Michael J.; Griffith, Kereen T.; Grace, James B.; Howard, Rebecca J.; Stagg, Camille L.; Enwright, Nicholas M.; Krauss, Ken W.; Gabler, Christopher A.; Day, Richard H.; Rogers, Kerrylee
Abstract: Climate greatly influences the structure and functioning of tidal saline wetland ecosystems. However, there is a need to better quantify the effects of climatic drivers on ecosystem properties, particularly near climate‐sensitive ecological transition zones. Here, we used climate‐ and literature‐derived ecological data from tidal saline wetlands to test hypotheses regarding the influence of climatic drivers (i.e., temperature and precipitation regimes) on the following six ecosystem properties: canopy height, biomass, productivity, decomposition, soil carbon density, and soil carbon accumulation. Our analyses quantify and elucidate linear and nonlinear effects of climatic drivers. We quantified positive linear relationships between temperature and above‐ground productivity and strong positive nonlinear (sigmoidal) relationships between (1) temperature and above‐ground biomass and canopy height and (2) precipitation and canopy height. Near temperature‐controlled mangrove range limits, small changes in temperature are expected to trigger comparatively large changes in biomass and canopy height, as mangrove forests grow, expand, and, in some cases, replace salt marshes. However, within these same transition zones, temperature‐induced changes in productivity are expected to be comparatively small. Interestingly, despite the significant above‐ground height, biomass, and productivity relationships across the tropical–temperate mangrove–marsh transition zone, the relationships between temperature and soil carbon density or soil carbon accumulation were not significant. Our literature review identifies several ecosystem properties and many regions of the world for which there are insufficient data to fully evaluate the influence of climatic drivers, and the identified data gaps can be used by scientists to guide future research. Our analyses indicate that near precipitation‐controlled transition zones, small changes in precipitation are expected to trigger comparatively large changes in canopy height. However, there are scant data to evaluate the influence of precipitation on other ecosystem properties. There is a need for more decomposition data across climatic gradients, and to advance understanding of the influence of changes in precipitation and freshwater availability, additional ecological data are needed from tidal saline wetlands in arid climates. Collectively, our results can help scientists and managers better anticipate the linear and nonlinear ecological consequences of climate change for coastal wetlands.